Sejarah Hak Asasi Manusia di Indonesia - Ismi Marhamah; Meri Mardiyani; Selina April liani; Wahyu Maulana (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The history of human rights in Indonesia is long and complex. Since the colonial era, human rights were not fully recognized and Indonesians were treated as slaves and excluded from political life. After independence in 1945, Indonesia recognized human rights in its constitution and joined the United Nations (UN) in 1950. During the Soekarno administration, human rights were considered part of Indonesia's ideology of nationalism and socialism. However, during the New Order era under Soeharto, human rights were ignored and often violated by the government and security forces. In the early 1990s, a reform movement emerged that demanded the recognition and protection of human rights. This sparked change in Indonesia and in 1998 Soeharto stepped down from power. Since reformasi, Indonesia has made much progress in promoting and protecting human rights, including the establishment of the National Human Rights Commission in 1993 and the ratification of a number of international treaties related to human rights. Nonetheless, many human rights violations still occur in Indonesia, such as violence and discrimination against minority groups and a lack of civil and political freedoms in some areas. As a developing democratic country, Indonesia still has challenges in protecting and promoting human rights as a whole. However, with the support of civil society, human rights organizations, and the commitment of the government, Indonesia can continue to improve and enhance human rights protection in the country.Â